Identification of ecosystem services in agricultural production: a study in agroflorestrial systems (Research, Society and Development, 2020)
The objective of this work was to identify and measure the ecosystem services provided by agroforestry systems when compared to a monoculture and a primary forest area from selected parameters in the study areas. The choice of indicators used the principles that they must be able to respond accurately to environmental variables to be analyzed, be financially applicable and present clear and objective results. These parameters were: i) soil quality analysis (pH, P, K, Na and Cot); ii) carbon sequestration by tree biomass; iii) generation of timber raw material for commercialization; and iv) increase of biodiversity by the Shannon-Weiner index. These parameters were analyzed in four study areas located in the Santa Bárbara municipality (PA), being an AFS in alley, a multi-layer SAF, an açai monoculture and a forest, all belonging to a settlement community. As results, both SAFs presented better soil quality for three parameters (pH, P and K) when compared to monoculture. The comparison between SAFs showed that the multi-stratified has higher carbon stored in the aerial biomass and commercial timber volume. Biodiversity, in turn, both SAFs presented four times greater Shannon Index than monoculture (SAF.A = 1.44 and SAF.AM = 1.49), but still considered low when compared to areas in regeneration or natural ecosystems of literature. Factors such as area history, age between SAFs and reduced size of the sampled areas may have influenced the variation of the results.